Predictors of caspofungin exposure-response relationship: a retrospective cohort study on therapeutic drug monitoring parameters - Meng, Mingwei; Wei, Ruhua; Lu, Yating; Cao, Wen; Mo, Kai; Huang, Zheng; Qin, Yane; Lan, Xiaobu (Frontiers in Pharmacology, 2025)
IntroductionThis study aimed to characterize the exposure-response relationship of caspofungin through analysis of trough serum concentration (Cmin) associated with clinical efficacy, while identifying clinically determinants of Cmin.MethodsA single-center retrospective cohort study collected therapeutic drug monitoring data from 83 hospitalized patients receiving caspofungin therapy between January 2022 and January 2025. Spearman correlation analysis and the receiver operating characteristic (ROC) curve were employed to evaluate associations between trough serum concentrations and clinical endpoints, with concomitant assessment of binary logistic regression analysis of determinants affecting interindividual exposure variability.ResultsA total of 83 eligible cases were included, with 51 cases in the effective treatment group and 32 cases in the ineffective group. The median caspofungin Cmin in the effective group was 5.62 [4.54, 7.0] μg/mL, while that in the ineffective group was 2.43 [1.61, 3.03] μg/mL. Spearman correlation analysis revealed a positive correlation between caspofungin Cmin and clinical efficacy, with r = 0.8 and p < 0.01. The ROC curve for caspofungin Cmin was 0.974, with a maximum Youden index of 0.816, corresponding to a cutoff value of 3.58 μg/mL, a sensitivity of 94.1%, and a specificity of 87.5%. Binary logistic regression analysis showed that patient body weight [OR = 0.839 (0.765∼0.921), p < 0.001] was an influencing factor of caspofungin Cmin.ConclusionCaspofungin trough serum concentration is correlated with its efficacy. Maintaining a trough concentration of caspofungin greater than 3.58 μg/mL within the dosing interval may achieve better clinical efficacy. Additionally, patient body weight should be considered when optimizing the dosing regimen due to its impact on drug concentration.